Rainfall Analysis as a Hydrological Cycle in Mine Drainage: Implications for Mitigating Nickel Mining Damage in Pomalaa, Southeast Sulawesi Province, Indonesia - Jumbadi Jumbadi; Erwin Setiawan; R.A.T. Listyani (CV FOUNDAE, 2025)
Inadequate mining management can harm the surrounding environment, including runoff that transports materials from mining sites to bodies of water or the sea. To prevent environmental damage, it is essential to implement mitigation measures in the mining area, such as constructing settling ponds. The research aims to understand the hydrological cycle in the context of nickel mining and develop strategies to mitigate environmental damage caused by mining activities. By examining rainfall data and its effects on mine drainage, the study seeks to provide insights into effective water management practices that can minimize the negative impacts of nickel mining on the environment. The data used is the value of rainfall for 10 years (2008 – 2017). The analysis was carried out on rainfall, runoff water discharge, and the rain catchment area. The results showed that the hydrological risk was 95.76% for the 10-year return period, the average rainfall was 119.84 mm, the designed rainfall was 175.85 mm, and the rain intensity was 38.41 mm/hour. The total discharge of runoff water in the north mine is 13.39 m3/sec, the middle is 25.34 m3/sec and the south is 11.02 m3/sec. The settling pond is designed in three working areas, namely the northern (991.72 m2), central (1,877.33 m2), and southern mining (816.241 m2) areas.